Maternal reproductive performance and fetal development of the Wistar Audiogenic Rat (WAR) strain - Umeoka, Eduardo H.; Eiras, Matheus C.; Viana, Iara G.; Giorgi, Vanessa S.; Bueno, Aline; Damasceno, Débora Cristina [UNESP]; Garcia-Cairasco, Norberto; Navarro, Paula A. (Taylor & Francis, 2018)
Wistar Audiogenic Rat (WAR) strain is an animal model for epilepsy studies, the chronic multifactorial disease that affects millions of people worldwide. The animals of this strain are genetically predisposed to sound-induced seizures, called audiogenic seizures, and have been used for many years in studies to understand the mechanisms involved in the epilepsies and their neuropsychiatric comorbidities, as well as the screening of potential anti-convulsant agents. Nevertheless, little is known about the reproductive characteristics of these animals. The main goal of this study was to characterize the female reproductive performance and the fetal growth of WARs in comparison to the Wistar rats, obtaining important information for physiology and behavioral studies, as well as for the preservation of the strain. The results indicated few differences between WAR and Wistar regarding the female reproductive performance. There was no significant difference in the number of pregnant females by mating, number of live births per female, number of cells per blastocyst, and several characteristics related to reproductive performance, such as pre- and post-implantation losses. However, significant differences were observed in birth weight and weight gain until weaning, with WAR animals presenting a body weight below Wistar at birth and reduced body weight gain during the lactation period. In addition, the WAR females showed lower body weight on the day 20 of pregnancy and a larger number of corpora lutea, when compared with those of Wistar animals. Thus, we conclude that although Wistar and WAR strains have few differences in their reproductive performance, which might impact future physiological life challenges or others experimentally induced procedures, it still is a very viable strain regarding reproduction. Abbreviations: CONCEA: National Council for the Control of Animal Experimentation; GEPR: genetically epilepsy-prone rats; WAR: Wistar Audiogenic Rat.
Keywords: audiogenic seizures; embryos; epilepsy; fetal development; reproductive performance; Wistar Audiogenic Rat (WAR)